N-Arylation of protected and unprotected 5-Bromo-2-aminobenzimidazole as organic material: Non-Linear Optical (NLO) properties and structural feature determination through computational approach - Mumtaz, Mubeen; Rasool, Nasir; Ahmad, Gulraiz; Kosar, Naveen; Rashid, Umer (MDPI, 2021)
The interest in the NLO response of organic compounds is growing rapidly, due to the ease of synthesis, availability, and low loss. Here, in this study, Cu(II)-catalyzed selective N-arylation of 2-aminobenzimidazoles derivatives were achieved in the presence of different bases Et3N/TMEDA, solvents DCM/MeOH/H2O, and various aryl boronic acids under open atmospheric conditions. Two different copper-catalyzed pathways were selected for N-arylation in the presence of active nucleophilic sites, providing a unique tool for the preparation of NLO materials, C-NH (aryl) derivatives of 2-aminobenzimidazoles with protection and without protection of NH2 group. In addition to NMR analysis, all synthesized derivatives (1a–1f and 2a–2f) of 5-bromo-2-aminobenzimidazole (1) were computed for their non-linear optical (NLO) properties and reactivity descriptor parameters. Frontier molecular orbital (FMO) analysis was performed to get information about the electronic properties and reactivity of synthesized compounds.